Implementation of Cooperative Script Learning Model to Improve News Listening Ability Students of Class X1-IPS SMA Negeri 14 Maluku Tengah - Everhard Markiano Solissa (Budapest International Research and Critics University, 2022)
This research is a quantitative descriptive study with a correlational design. The purpose of this study was to describe the differences in the ability to listen to the news of students in class XI-IPS SMA Negeri 14 Maluku Tengah. Data was collected by using observation, questionnaire, and test techniques. The samples of this research were students of class XI IPS-1 (23 people) and students of class XI IPS-2 (20 people). Data analysis was carried out using SPSS version 20. The results of this study were (1) the average posttest score for the experiment class was higher than the average posttest score for the control class; (2) there was an increase in the average score in the experiment class from 81.98 to 88.10; (3) the normality test and homogeneity test showed that the data were normally distributed because the significance value was more than 0.05; (4) there is a strong and significant correlation between the results of the pretest and posttest in the experiment class.